Letter (copy) : Harrison's pomade - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0076-001 S.M.A.C. 25th February, 1938. Professor, J.B.S. Haldane, 54, Fitzroy Road, LONDON, N.W.1 Dear Professor Haldane, Harrison's Pomade. At the last meeting of the Spanish Medical Aid Committee some correspondence was submitted from Mrs. Charlotte Haldane, recommending (said to be with your approval) the sending out by the Spanish Medical Aid Committee of a considerable quantity of this Pomade, with a view to its use by the Spanish Army and soldiers in the trenches from the point of view of disinfestation. I will be very much obliged if you can possibly tell me whether any experiments have been conducted as to the value of this substance in disinfestation or even in minimising the discomforts of infestation. Two Medical members of the Committee (one of which is myself) asked from our own personal experience that a vote against this recommendation should be recorded, but as it came from you an order was placed for some quantity of the material to be sent out to Spain. I am keenly interested in the subject of disinfestation, and have been going into it for some time, and if you can give me any information as to the value of this particular article or any literature or experiments done in the subject showing the exceptional qualities of this preparation, I should be very much obliged. Yours sincerely, H.B.M EK Further letters in pink folder "Disinfestation" (top drawer) 292C/946/2/76